Analysis Of Potential Hazards In Boiler Parts Using Hirarc In Steam Power Plant (PLTU) Units Sebalang Generator Executor - Muhammad Suhendra Wijaya; Nova Mega Rukamana; Nur Sefa Arief (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
In every workplace there is always a risk of accidents, which are related to company activities. Accidents are usually caused by people who do not meet company standards and unsafe environmental conditions. There is a potential danger which can cause work accidents. The aim of this research is to find out how to analyze potential hazards in the PLTU boiler section using HIRARC at the PLTU Nusantara Power Sebalang Generation Implementation Unit. This is qualitative research, with the approach used, namely observation and gathering information through in-depth interviews regarding potential dangers and safety risks to workers in the PLTU, the Sebalang generation implementing unit in the boiler unit. Then the HIRAR method was used. There were 6 informants consisting of 1 main, 3 key and 2 supporting informants using a purposive sampling technique. The instruments used were observation sheets regarding hazard identification, risk assessment and control, as well as HIRARC based on the provisions of PT PLN Nusantara Power Pusat. Results: In the boiler section of the Sebalang Power Plant Implementation Unit, there are potential hazards, namely physical hazards, chemical hazards and psychological hazards. Risk assessment with accumulated risk levels and severity levels based on PT PLN Nusantara Power Pusat's assessment. With elimination, substitution, engineering, administrative and PPE controls. Potential dangers that occur in the work environment: physical dangers (noise, extreme temperatures and exposure to coal dust ) , mechanical dangers (falling, slipping and tripping from heights and electric shocks), chemical dangers and psychological dangers from stress levels/workload.